MEDU-15. CCL2/CCR2/IL-6 LOOP: A POTENTIAL THERAPEUTIC TARGET FOR PEDIATRIC MEDULLOBLASTOMAS - Bredlau, Amy-Lee (Neuro Oncol, 2017)
Medulloblastoma cells in situ are surrounded by microglia, suggesting medulloblastoma–microglia interactions to produce various outcomes. As chemokines are important mediators of cell–cell communication, we sought to identify common chemokines in mouse and human medulloblastoma lines. We found CCL2 (chemokine (C-C motif) ligand 2) messenger RNA was expressed by Group 3 and 4 medulloblastoma lines. However, these lines did not express the CCL2 receptor, CCR2, which was found on microglia. The MP-1 medulloblastoma cell line expresses low basal levels of CCL2. Hence, we overexpressed CCL2 plasmid with GFP tagging in MP-1 medulloblastoma cells to investigate the hypothesis that medulloblastoma-secreted CCL2 interacts with microglia to affect medulloblastoma growth and invasion. In medulloblastoma–microglia co-culture models, we observed increased proliferation of CCL2-overexpressing clones. ELISA protein analyses revealed that interleukin-6 (IL-6) was consistently increased in the co-culture. Recombinant IL-6 enhanced the invasion of medulloblastoma cells when these were cultured alone, whereas a neutralizing antibody to IL-6 attenuated the microglia-stimulated medulloblastoma invasion. This study reveals a mechanism by which medulloblastoma cells exploit microglia (M2-phenotype) for increased invasion. Specifically, medulloblastoma-derived CCL2 acts upon CCR2-bearing tumor associated microglias (TAMs), which produce IL-6 to stimulate medulloblastoma cells, in a CCL2/CCR2/IL-6 loop. We targeted this loop by combining radiation therapy with a 4-1BB (CD-137) monoclonal antibody (mAb), as CD-137 is involved in regulation of immune cell proliferation and survival. We re-educated microglia cells toward a cytotoxic M1-like phenotype and amplified effective anti-tumor immune responses in co-culture models. ELISA spot shows treatment with 50 ng of 4-1BB + 1Gy X-ray radiation converted the microglia from M2 to M1 phenotype via a decrease in CCR2. This treatment induces the M1 phenotype microglia to induce MP-1 cell death. Based on our results, the use of 4-1BB mAb plus radiation may prove to be beneficial for the treatment of medulloblastoma by targeting CCL2/CCR2/IL-6 loop.